Sustainable Use of the Environment, Planetary Boundaries and Market Power - Edward B. Barbier (Sustainability, 2021)
Many of the environment and natural resources that constitute key “safe operating spaces”, as designated by planetary boundaries, are being exploited by a handful of large firms with considerable market share. In this paper, we discuss how the environment and natural resources that occur within a safe operating space can be treated as an exploitable finite stock. We use an optimal depletion model to show how the extraction of these exhaustible assets can be managed optimally, and allow for adjustment in price paths due to technological innovation and environmental externalities. Given the growing market concentration and monopoly power in the key economic sectors that exploit the environment and resources that constitute many safe operating spaces, we then explore how monopoly conditions can alter the extraction and price path of the environmental assets over time compared to that under competitive market conditions. We show that the monopoly may be compatible with more sustainable use, by extending the life of the exploitable, depletable stock, at the expense of firms capturing excessive resource rents from exploitation. This tradeoff means that any policies implemented to tax the excessive monopoly rents need to be designed without compromising the sustainable use of the environment. The tax revenue raised can be channeled into protecting or regenerating natural assets that are essential for global environmental sustainability. If investment in regeneration efforts is sufficiently substantial, or if the wider social and environmental values associated with the exhaustible assets are taken into account, then the safe operating space may be conserved indefinitely. Such policy challenges will become increasingly important as dominant firms exert market power over the planet’s remaining environment and resources that constitute key “safe operating spaces”, as designated by planetary boundaries.